The effect of company responses to social media negative word of mouth: A text mining approach - Correia, Liliane Patrícia Lopes (2019)
Word-of-mouth (WOM) is emerging in importance for brand reputation and understanding of consumer behavior. Motivations to engage in WOM has been largely studied in marketing literature. How companies respond to WOM online was accounted in marketing literature to deliver distinguishing managerial response strategies to brands. This research project focuses on identifying which response strategy is the most crucial to make customers satisfied after a negative WOM. Text mining and sentiment analysis were used in order to draw conclusions from actual online consumer behavior. Negative WOM (NWOM) was extracted from different brand pages on Facebook, as well as the responses from the companies to these NWOM and the reaction from the NWOM’s writer to the brand’s response. A literature-based framework using Davidow's Facilitation, Apology and Attentiveness, and Benoit's Corrective Action was tested on the data. Further moderation analysis was conducted to test effects of NWOM’s polarity and industry on the relationship between the responses and satisfaction. Results reveal that Facilitation is important to response satisfaction. Whenever brands re-directed original NWOM writers to formal complaint means, their satisfaction increased. This was especially true for hospitality and e-commerce industries. Reversely, for hospitality and e-commerce industries, Apology had a negative impact on response satisfaction. Results yielded that Attentiveness decreased response satisfaction when polarity was a moderator. Managers should provide effective means for consumers to voice their disappointment and not rely on apologies alone. Future research should tackle more in depth the intricacies of languages and the distinction of complainers and brand haters on response strategies.